Dream types a domain specific type system for component-based message-oriented middleware. - Bidinger, Philippe
We present a type system for the Dream component-based message-oriented middleware. This type system aims at preventing the erroneous use of messages, such as the access of missing content. To this end, we adapt to our setting a type system developed for extensible records.
Keywords: Software; Software Engineering; Software architectures; Domain-specific architectures; Languages (e.g., description, interconnection, definition).; Interoperability; Design